Evaluation of the 2020 European Academy of Neurology virtual congress: transition from a face‐to‐face to a virtual meeting. (11th June 2021) - Stamelou, Maria; Struhal, Walter; ten Cate, Olle; Matczak, Magdalena; Çalışkan, Süleyman Ayhan; Soffietti, Riccardo; Marson, Anthony; Zis, Panagiotis; di Lorenzo, Francesco; Sander, Anja; Deuschl, Günther; de Visser, Marianne; et al.
Abstract: Background and purpose: Due to the COVID‐19 pandemic, scientific congresses are increasingly being organized as virtual congresses (VCs). In May 2020, the European Academy of Neurology (EAN) held a VC, free of charge. In the absence of systematic studies on this topic, the aim of this study is to evaluate the attendance and perceived quality of the 2020 EAN VC compared to the 2019 EAN face‐to‐face congress (FFC). Methods: An analysis of the demographic data of participants obtained from the online registration was done. A comparison of the two congresses based on a survey with questions on the perception of speakers' performance, quality of networking and other aspects was made. Results: Of 43, 596 registered participants, 20, 694 active participants attended the VC. Compared to 2019, the number of participants tripled (6916 in 2019) and the cumulated number of participants attending the sessions was five times higher (169, 334 in 2020 vs. 33, 024 in 2019). Out of active participants 55% were from outside Europe, 42% were board‐certified neurologists (FFC 80%) and 21% were students (FFC 0.6%). The content of the congress was evaluated as 'above expectation' by 56% of the attendees (FFC 41%). Of the respondents who had been exposed to earlier EAN congresses 73% preferred the FFC compared to the VC (17%). Conclusion: The VC fulfilled the main mission of organizing high quality EAN congresses despite the restrictions of the impersonal format. The geographical distribution of the participants proves the expected higher inclusivity of a VC. The large participation of students and neurologists in training opens new educational potentials for the EAN. Abstract : In this study, a comparison between the first virtual EAN congress (VC) with the previous face‐to‐face congress (FFC), based on a survey with questions on the perception of speakers' performance, quality of networking and other aspects, was made. Compared to 2019, the number of participants of the virtual congress tripled. Participants came from all continents, suggesting higher inclusivity compared to FFC. Moreover, participants represented all stages of academic career with a significantly higher number of students and young trainees compared to FFC, which is crucial for the educational role of EAN. The content of the congress was evaluated as 'above expectation' by 56% of the attendees (FFC 41%). Overall, the virtual congress fulfilled the main missions of EAN.